Microstructure evolution, solidification characteristic and magnetocaloric properties of MnFeP0·5Si0.5 particles by droplet melting. (April 2021) - Tu, Defang; Li, Jun; Zhang, Ruiyao; Hu, Qiaodan; Li, Jianguo
Abstract: Mn–Fe–P–Si compounds are promising magnetocaloric materials for magnetic refrigeration. However, the microstructure evolution and solidification characteristics are rarely discussed in the literature. Here, we investigate the solidification characteristics and microstructure evolution of MnFeP0·5 Si0.5 alloys under different undercooling and cooling rates based on droplet melting method. Results show that the alloy solidifies in the sequence of Fe2 P phases, (Fe2 P+(Mn, Fe)5 Si3 ) eutectics and (Fe2 P+(Mn, Fe)3 Si eutectics. With the increase in undercooling and cooling rate, the (Fe2 P+(Mn, Fe)5 Si3 ) and (Fe2 P+(Mn, Fe)3 Si) eutectic growth is divorced, and the Fe2 P phase experiences from coarse strips to fine dendrites, then fragmented dendrites, and finally to equiaxed dendrites. Besides, the volume fraction of the Fe2 P phase increases, and its atomic ratio approaches the nominal composition. As the droplet diameters decrease, we find a drop in Curie temperatures (228-210 K) and an increase in hysteresis (4–11 K). The magnetisation of the 500 μm droplet is also up to 51 Am 2 /kg. These results indicate that the magnetocaloric properties of the alloys strongly depend on the phase-type, morphology and composition evolution. Additionally, the operating temperature range and the refrigerant capacity of the 500 μm droplet are as high as 41 K and 112 J/kg, respectively, which will benefit the practical application of Mn–Fe–P–Si alloys. Highlights: A new method, droplet melting, was used to prepare the MnFeP0·5 Si0.5 droplets. Different undercooling and cooling rate were obtained to control the microstructures of MnFeP0·5 Si0.5 droplets. The microstructure evolution and solidification characteristics of MnFeP0·5 Si0.5 alloys were first revealed. The magnetocaloric properties can be effectively adjusted by controlling the microstructure of the droplets.